Right to Education in Ukraine: 2015–2019 reforms and following steps - Kovtunets, Volodymyr; Shevtsov, Andrii (Pázmány Law Review, 2023)
This article primarily focuses on a constitutional review of the current Ukrainian Education system. It has a strong historical approach starting from the collapse of the Soviet Union. The authors analyse the reform attempts occurred in the most recent decade in a critical way and show how and why has the attitude of the governments changed in the mid 2010s and how the Ukrainian education entered the war in 2022.